Technology Development for Conservation, Propagation and Adaptation of Native Crops to Biotic and Abiotic Stress Factors: Concept, Hypothesis and Confirmation - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2023)
The ever increasing human population under the changing Climate, Global Warming, Pollution, Biotic and Abiotic Stress, Drought and Salinity is facing an acute threat for Global Food Security. The focus of the breeders has always been on increased food production. It started with identifying high yielding varieties and production of hybrids…